Sanksi Administrasi Dalam Surat Edaran - Ely, Maya Wulandari; Pietersz, Jemmy Jefry; Bakarbessy, Andress Deny (LUTUR Law Journal, 2023)
Introduction: The phenomenon of ministerial circulars in the hierarchy of laws and regulations in Indonesia has never been concretely embodied in the order of laws and regulations. This was caused by the debate over the ministerial circular letter, whether the circular letter was included in the category of regulation (regeling) or stipulation (beschiking). The essence of a Circular Letter is part of a policy regulation that contains notifications or explanations or technical instructions for carrying out a matter and only applies internally to government organizations, is not regulatory and applies outwardly and binds the general public like a statutory regulation. Circulars are informative in the implementation of certain government affairs Purposes of the Research: The objectives of this study are: To study and analyze the content of Administrative Sanctions in Circulars and To study and analyze the Legal Power of Circulars that have Administrative Sanctions Methods of the Research: This research is normative juridical. Library materials are the basis for research (knowledge) classified as secondary data. The secondary data intended in this study are in the form of personal letters, books, official documents, literature, scientific papers and laws and regulations to complete this writing. Results / Findings / Novelty of the Research: Research shows that although the existence of a Circular Letter as an informative official document in an internal government organization is made by a superior official to a subordinate official to carry out a certain government affair, a Circular Letter can also contain Administrative Sanctions whose legal force is in Law Number 30 2014 concerning Government Administration